Inflation Targeting and Output Growth : Empirical Evidence for the European Union. (IMF Working Papers; Working Paper ;, 2005)
This paper evaluates the performance of two alternative policy rules, a forward-looking rule and a spontaneous adjustment rule, under alternative inflation targets, in terms of output losses in a macroeconomic model, using European Union data. The simulations suggest that forward-looking rules contribute to macroeconomic stability and monetary policy credibility, and that a positive inflation target, as opposed to zero inflation, leads to higher and less volatile output. These results are robust to changes in the specification of the model and time period. The same methodology applied to individual countries supports country-specific flexible inflation targeting.